The Incident of Depression In Post Stroke Patients In the Nervous Polyclinic Room of Daya General Hospital Makassar City, South Sulawesi - Hastutiningtyas, Wahidyanti Rahayu; Betan, Abu Bakar; Abdullah, Abdullah; Aisyah, Siti; Ayu, Nur Meity Sulistia; Noviar, Rizki Andita; Mulia, Madepan; Latif, Sarifudin Andi (International Journal of Health Sciences, 2024)
Stroke is a disorder of blood circulation in the brain, either due to ischemic (non-hemorrhagic stroke) or hemorrhagic (hemorrhagic stroke), which causes a lack of blood supply to the brain. Depression is an emotional disorder experienced by a person that can make him feel sad and helpless. The prevalence of stroke in Indonesia is 12.1 ‰, the highest in the province of South Sulawesi (17.9‰) and the lowest in the provinces of West Papua, Lampung and Jambi (5.3‰). The aim of this study was to determine the description of the incidence of depression in post-stroke patients in the Neurology Clinic at Makassar Hospital. The type of research used in this research is descriptive survey research. The instrument in this research uses a questionnaire. The sample in this study was 38 post-stroke patients taken using accidental sampling technique. The results of this study showed that of the 38 respondents (100.0%), 33 respondents (86.8%) were Ischemic (Non-Hemorrhagic Stroke) and 5 respondents (13.2%) were Hemorrhagic (Hemorrhagic Stroke). For the incidence of depression, from 38 respondents (100.0 %), the highest incidence of depression was mild depression, 9 respondents (23.7%) and the lowest was 6 respondents who were not depressed (15.8%). The conclusion of this research is that the incidence of depression in post-stroke patients at the Makassar Hospital Neurology Clinic is that the majority experienced non-hemorrhagic strokes and the majority had mild depression. Patients are advised to reduce or prevent atherosclerosis and Obstructive Sleep Apnea while sleeping by maintaining a lifestyle such as exercising frequently, maintaining body weight, and having regular health check-ups at health facilities. This is useful for avoiding ischemic strokes or Non-Hemorrhagic Strokes. and it is recommended that respondents always view the stressors they experience positively.